PERENCANAAN PEMBELAJARAN BERDIFERENSIASI YANG BERPUSAT PADA MURID PADA JENJANG PENDIDIKAN ANAK USIA DINI (PAUD) - Nur'aini Muhassanah; Muhammad Nur Rizal; Musyafa Ali (Jurnal Tumbuh Kembang Anak Usia Dini, 2023)
Differentiated learning is a way for teachers to meet the needs of each student because differentiated learning is a teaching and learning process where students can learn subject matter according to their abilities, what they like and their individual needs so that they do not get frustrated and feel like they have failed in their learning experience. This research aims to plan differentiated learning that is centered on students at the Early Childhood Education level. The method in this research uses a qualitative approach with a literature study type of research. Data collection in this research refers to secondary sources in the form of books or journal articles as well as primary sources of data on plans to build a school ecosystem as well as plans for implementing student-centered learning practices by school supervisors, school principals and teachers who are included in the Driving School Program. The result of this research is that in implementing the curriculum in the classroom, educators can use differentiated learning to group students' readiness, interests and also children's learning profiles/styles. Differentiated learning emphasizes the learning process by referring to four differentiated components, namely content, process, product and learning environment. The results of the plan to build a student-centered school ecosystem were six policy plans, objectives, implementers, and steps in creating a child-centered learning ecosystem carried out by PAUD supervisors and principals. Apart from that, teachers have also planned student-centered learning practices by paying attention to students' interests, learning styles and learning readiness, which consists of learning objectives, morning habits, preliminary activities, core activities, closing activities, as well as assessment/assessment. is in accordance with the Merdeka curriculum.